Interleukin-17 Produced by Malignant Mesothelioma-Polarized Immune Cells Promotes Tumor Growth and Invasiveness. (January 2013) - Izzi, V.; Chiurchiù, V.; Doldo, E.; Palumbo, C.; Tresoldi, I.; Bei, R.; Albonici, L.; Modesti, A.
Malignant mesothelioma (MM) is a highly fatal tumor of inner body membranes, the extensive growth of which is supported by both a weak immunogenicity and the ability to reprogram surrounding immune cells towards tumor-supporting phenotypes. Interleukin-17 (IL-17) is a major inflammatory cytokine which is now accepted as the paradigmatic cytokine of many autoimmune diseases; however, its role in tumor immunology has only been partially unraveled, and no data exist regarding its possible involvement in MM. Thus, in this work we evaluated the ability of MM to induce IL-17 production in immune cells and the effects of IL-17 on MM growth and invasiveness. Our data show for the first time that macrophages and CD4 + T-cells are polarized by MM to produce IL-17, and that this cytokine exerts multiple tumor-supporting effects on both cell growth and invasiveness. These data provide novel evidence of the crosstalk occurring between MM and immune cells and suggest potential targets for the development of new pharmacological approaches for MM treatment.